THE INFLUENCE OF SOCIAL MEDIA, STORE ATMOSPHERE AND PROMOTIONS ON REPURCHASE INTEREST IN PAON SIYAP KARUNIA PRODUCTS IN SURABAYA - Gunawan, Kelly; Kiara, Calandra; Sutanto, J.E. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to examine the impact of social media, store atmosphere and promotion on repurchase intention for Paon Siyap Karunia products. The study used quantitative methods to test between research variables. Paon Siyap Karunia is a food business that sells Indonesian food from 2020. The population used in this study were people who had bought Paon Siyap Karunia products, with a sample of 150 respondents. Data was collected using google form. This study uses purposive sampling techniques and non-probability sampling methods. Data was processed using SPSS 26. The result showed that social media has an effect on repurchase interest, which shows that managing social media to be better and more attractive can increase repurchase interest. The result showed that store atmosphere has an effect on repurchase interest, which shows that having a comfortable place can increase repurchase interest. The result showed that promotion has an impact on repurchase interest, which provides evidence that appropriate and attractive promotions can increase repurchase interest. And the results on social media, store atmosphere and promotions affect the interest in repurchasing Paon Siyap Karunia products.